Accounting Students, Social Media and Online Learning in West Africa’s Topmost University - Odiboh, Oscar; Alege, Philip; Fasanya, Opeyemi; Adegoke, Kayode; Afolabi, Oluwafolafunmi; Ofor, Anita (International Journal of Social Sciences Perspectives, 2020)
All over the world, accounting students have the burden of scholarship and professional studies in order to become future accountants. A way to cope with this demand is to use the ubiquitous social media. This study examined the demographic differentials in the students' awareness and usage of social media as online pedagogical tools. Purposely selected for the study were accounting students of Covenant University, ranked number one in West Africa by the 2019 Times Higher Education. The university enrols its accounting undergraduates for external professional examinations additionally to four years of a degree course. A quantitative methodology using a survey technique afforded the application of a questionnaire instrument in the study. The Scientific Package of Social Sciences was used to analyse the data gathered from 294 students of accounting across gender, age and levels of studentship. Results point out that accounting students are aware of the educational value of social media outlets. However, in practice, online platforms are lowly used for learning purposes. While students mostly subscribe to Instagram, YouTube is the most valuable media for learning. More than gender and level of studentship, influence both awareness and usage of social media for undergraduates' online learning. The study concludes that socio-pragmatic considerations rather than epistemic consciousness determine students' social media affiliations and usage. Resulting recommendations are: that international researches should study the applicability of social media as online learning apparatuses. Also; educational administrators should rethink social media as online pedagogical tools.